Design-based system performance assessment of a combined power and freshwater cogeneration system - Elfizon, Elfizon; Nuñez Alvarez, José Ricardo; Chammam, Abdeljelil; Al-Kharsan, Ibrahim H.; Jweeg, Muhsin J.; Yánez-Moretta, Patricio; Alayi, Reza; Khan, Imran; Byun, Yung-Cheol; Madsen, Dag Øivind (Frontiers in Energy Research, 2023)
In this research, the design and use of combined systems for the simultaneous production of water, heat, and energy have been proposed, and, to fulfill the water, electricity, and heat demands of a hotel, modeling of the multi-effect evaporative desalination (MED) and combined heat and power (CHP) generation system was done. Then, the design of these two systems was administered in a combined way. This design was applied in order to evaluate the economy of the combined system compared to separate systems. The performed scenario was executed every 24 h during the two seasons of the year. The genetic algorithm was used to optimize this system, and it was considered the objective function to minimize the annual costs. The results showed that the nominal capacity of the gas turbine and backup boiler in the CHP + MED + thermal energy storage (TES) system was (14%) larger and (8.2%) smaller, respectively, compared to the CHP+ MED system. In addition, by using the energy storage tank in the combined CHP + MED system, 5.1% of the annual costs were reduced.